Strategic management : state of the field and its future - Duhaime, Irene M.; Hitt, Michael A.; Lyles, Marjorie A. (New York, N.Y. : Oxford University Press, 2021)
"This contributed volume provides the knowledge portfolio for the Strategic Management field. Strategic Management has experienced significant growth as a research discipline and builds on strong theoretical and empirical research to provide valuable knowledge for managerial practice. The book is designed to capture the rich breadth and depth of knowledge in the field as well as insightful examinations of critical topics for the future and opportunities for future research (50% of the focus). Such information and knowledge are critical for all current and future scholars in the field and for thoughtful executives as well. The 37 chapters by well-known and highly respected scholars capture the essence of the field. They address the field's evolution, the primary economic and organization theories underlying the base of knowledge and the critical methodologies used to conduct research. The chapters cover strategy topics of major importance (and their primary subtopics), such as corporate strategy (diversification, acquisitive growth, divestitures), strategic entrepreneurship (nascent firms, industry emergence, technology entrepreneurship), competitive and cooperative strategies (competitive advantage, alliances, networks), global strategy (multinational firms' cross-border strategies; strategies employed in emerging economies), strategic leadership (top management teams; CEO succession), governance and boards of directors (corporate and venture boards; ownership effects on governance), knowledge and innovation (organizational learning, knowledge sharing), strategy process and practice (strategic decision making, organizational change), and micro-foundations of strategy (strategic human capital, organizational capabilities). The book concludes with chapters on broadly important issues for the future such as artificial intelligence, sustainability strategies, stakeholder perspective, and business model innovation strategies"--
Includes bibliographical references and indexes.
Keywords: Strategic planning